Resolving the Tetrastigma loheri s.l. species complex (Vitaceae) in the Philippines: No evidence for recognizing more than one species - Obico, Jasper John; Barcelona, Julie; Bonhomme, Vincent; Hale, Marie; Pelser, Pieter (Dryad, 2020)
Tetrastigma loheri (Vitaceae) is a vine species native to Borneo and the
Philippines. Because it is a commonly encountered forest species in the
Philippines, T. loheri is potentially suitable for studying patterns of
genetic diversity and connectivity among fragmented forest ecosystems in
various parts of this country. However, previous research suggests that T.
loheri is part of a species complex in the Philippines (i.e. the T. loheri
s. l. complex) that potentially also contains Philippine plants identified
as T. diepenhorstii, T. philippinense, T. stenophyllum, and T.
trifoliolatum. This uncertainty about its taxonomic delimitation can make
it challenging to draw conclusions that are relevant to conservation from
genetic studies using this species. Here, we tested the hypothesis that T.
loheri s.l. is composed of more than one species in the Philippines. For
this, we used generalized mixed Yule coalescent (GMYC) and Poisson tree
process (PTP) species delimitation models to identify clades within DNA
sequence phylogenies of T. loheri s.l. that might constitute species
within this complex. Although these methods identified several putative
species, these are statistically poorly supported and subsequent random
forest analyses using a geometric morphometric leaf shape dataset and
several other vegetative characters did not result in the identification
of characters that can be used to discriminate these putative species
morphologically. Furthermore, the results of principal component and
principal coordinates analyses of these data suggest the absence of
morphological discontinuities within the species complex. Under a unified
species concept that uses phylogenetic and morphological distinction as
operational criteria for species recognition, we therefore conclude that
the currently available data do not support recognizing multiple species
in the T. loheri s.l. complex. This implies that T. loheri is best
considered as a single, morphologically variable species when used for
studying patterns of genetic diversity and connectivity in the
Philippines.
Files include: 1) A read me file (Readme_for_TetrastigmaDatasets.pdf)
for the datasets from Resolving the Tetrastigma loheri s.l.
Species Complex (Vitaceae) in the Philippines: No Evidence for Recognizing
More than One Species.  2) Zip file of the datasets
(Tetrastigma_datasets.zip). 3) Four supplemental figures (Figs. S1-S4.tif)
showing ITS, ETS, ITS-ETS, and plastid (atpB-rbcL, psbA-trnH, rps16, and
trnL-F) Bayesian inference trees for the
manuscript, Resolving the Tetrastigma loheri s.l. Species Complex
(Vitaceae) in the Philippines: No Evidence for Recognizing More than One
Species.
Keywords: Generalized mixed Yule coalescent; Poisson tree process